A new species of the genus Cyrtodactylus Gray, 1827 from central Laos (Squamata: Gekkonidae) - David, Patrick; Nguyen, Truong Quang; Schneider, Nicole; Ziegler, Thomas (Zootaxa, 2011)
A new species of the gekkonid genus Cyrtodactylus Gray, 1827, Cyrtodactylus teyniei spec. nov., is described based on a single adult female from Borikhamxay Province, central Laos. It is distinguished from any other Cyrtodactylus species by the combination of the following characters: (1) SVL 89.9 mm, (2) longitudinal rows of dorsal tubercles 19, (3) ventral scales in 38 rows between ventrolateral skin folds, (4) ventrolateral skin folds without tubercles, (5) enlarged femoral and precloacal scales 54 (precloacal scales 8, plus 23 femoral scales on each side), (6) precloacal depression lacking, (7) precloacal pores 14, (8) subdigital lamellae under the firth toe 19–20, (9) enlarged median subcaudals, and (10) nuchal band absent, dorsum with blotched pattern. An extended comparison with other species of the genus Cyrtodactylus, in particular species recently described from Laos and Vietnam, is provided. Cyrtodactylus teyniei spec. nov. is the seventh species of Cyrtodactylus known to occur in Laos.